Cortical pathology in multiple sclerosis detected by the T1/T2‐weighted ratio from routine magnetic resonance imaging. Issue 4 (16th September 2017) - Righart, Ruthger; Biberacher, Viola; Jonkman, Laura E.; Klaver, Roel; Schmidt, Paul; Buck, Dorothea; Berthele, Achim; Kirschke, Jan S.; Zimmer, Claus; Hemmer, Bernhard; Geurts, Jeroen J. G.; Mühlau, Mark
Abstract : Objective: In multiple sclerosis, neuropathological studies have shown widespread changes in the cerebral cortex. In vivo imaging is critical, because the histopathological substrate of most measurements is unknown. Methods: Using a novel magnetic resonance imaging analysis technique, based on the ratio of T1‐ and T2‐weighted signal intensities, we studied the cerebral cortex of a large cohort of patients in early stages of multiple sclerosis. A total of 168 patients with clinically isolated syndrome or relapsing–remitting multiple sclerosis (Expanded Disability Status Scale: median = 1, range = 0–3.5) and 80 age‐ and sex‐matched healthy controls were investigated. We also searched for the histopathological substrate of the T1/T2‐weighted ratio by combining postmortem imaging and histopathology in 9 multiple sclerosis brain donors. Results: Patients showed lower T1/T2‐weighted ratio values in parietal and occipital areas. The 4 most significant clusters appeared in the medial occipital and posterior cingulate cortex (each left and right). The decrease of the T1/T2‐weighted ratio in the posterior cingulate was related to performance in attention. Analysis of the T1/T2‐weighted ratio values of postmortem imaging yielded a strong correlation with dendrite density but none of the other parameters including myelin. Interpretation: The T1/T2‐weighted ratio decreases in early stages of multiple sclerosis in a widespread manner, with a preponderance of posterior areas and with a contribution to attentional performance; it seems to reflect dendrite pathology. As the method is broadly available and applicable to available clinical scans, we believe that it is a promising candidate for studying and monitoring cortical pathology or therapeutic effects in multiple sclerosis. Ann Neurol 2017;82:519–529